Motor control of spinal stability: Implications for the athlete - Hodges, P. (1999)
Stability of the lumbopelvic region is a critical element in sport performance. Every movement of the limbs or trunk challenges the integrity of the region and forceful contraction of the limb muscles requires a stable base. It is important to consider that stability is not a single entity and involves both the orientation of the entire spine and control of the intervertebral segments. Furthermore, the mechanisms used by the central nervous system to control these elements appear to be somewhat independent. There is considerable evidence in the literature to suggest that both the aspects of stability of the lumbar spine and pelvis are controlled in advance of movement when the movement is predictable and with short latency after the perturbation when forces are added to the spine in an unpredictable manner. It appears that contraction of the deep muscles (transversus abdominis and multifidus) occurs in advance of the superficial muscles to enhance segmental control to simplify the action of the superficial muscle in their role to control orientation. Thus for optimal control of the lumbopelvic region it is critical that both the deep and superficial muscles function appropriately. Several factors may interfere with this normal function that require consideration for the athlete. Firstly, changes in motor control occur in the presence of pain and secondly, many of the muscles involved in control of segmental stability are also have respiratory functions. When pain is present the timing of contraction of the deep muscles is changed. On the basis of evidence of the specific contribution of these muscles to stability it is hypothesised that this deficit in deep muscle control may lead to poor control of the intervertebral segments and potential for further microtrauma to the motion segment. In terms of respiration, activity of transversus abdominis and the diaphragm is coordinated to maintain respiration and segmental control concurrently. However, when the respiratory demand is increased (as occurs with exercise) the respiratory contribution of these muscles is increased and their ability to contribute to spinal control is reduced. Thus, for the athlete it is important to consider the control (as opposed to strength) of the deep and superficial trunk muscles as well as the integration between postural and respiratory functions of these muscles.